Selective and non-selective excitation/ionization processes in analytical glow discharges: excitation of the ionic spectra in argon/helium mixed plasmas - Mushtaq,S; Steers,EBM; Pickering,JC; Putyera,K (Journal of Analytical Atomic Spectrometry, 2013)
The increasing use of mixed gases, including helium mixtures, in glow discharge mass spectrometry has led to a need to understand the resulting signal enhancements due to changes in excitation and ionization processes. To understand more fully these processes in glow discharge, we have carried out complementary optical emission spectrometry experiments. The presence of added gases in the plasma gas can cause major changes in the number density of plasma gas ions and metastable atoms and so affects the intensities of spectral lines involving selective and non-selective excitation & ionization processes. We report the results of an experimental investigation on the effect of Ar/He mixed plasmas on the relative emission intensities of various analyte materials including copper, iron and titanium. Selective and non-selective excitation processes which are mainly dependent on the nature of the plasma gas and analyte material are observed and discussed.